2021
DOI: 10.2903/j.efsa.2021.6378
|View full text |Cite
|
Sign up to set email alerts
|

The use of the so‐called ‘superchilling’ technique for the transport of fresh fishery products

Abstract: Superchilling entails lowering the fish temperature to between the initial freezing point of the fish and about 1–2°C lower. The temperature of superchilled fresh fishery products ( SFFP ) in boxes without ice was compared to that of products subject to the currently authorised practice in boxes with ice ( CFFP ) under the same conditions of on‐land storage and/or transport. A heat transfer model was developed and made available as a tool to identify under which in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 144 publications
(239 reference statements)
0
5
0
Order By: Relevance
“…Liu et al [7] also found that superchilling storage can inhibit the growth of microorganisms and retard the hydrolysis of proteins more effectively than at 0 • C in grass carp fillets. Superchilling preservation technology has many advantages in preserving food, but the temperature fluctuation, repeated freezing and thawing caused by the instrumentation or external environment can have adverse effects on the protein quality of the product [8,9]. Therefore, it is necessary to combine other preservation technologies to meet the market requirements for the freshness of aquatic products.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [7] also found that superchilling storage can inhibit the growth of microorganisms and retard the hydrolysis of proteins more effectively than at 0 • C in grass carp fillets. Superchilling preservation technology has many advantages in preserving food, but the temperature fluctuation, repeated freezing and thawing caused by the instrumentation or external environment can have adverse effects on the protein quality of the product [8,9]. Therefore, it is necessary to combine other preservation technologies to meet the market requirements for the freshness of aquatic products.…”
Section: Introductionmentioning
confidence: 99%
“…Here temperature and growth have been modelled. Superchilling opinion (EFSA BIOHAZ Panel, 2021 ): https://www.efsa.europa.eu/en/efsajournal/pub/6378 . Here only temperature was modelled; no need for modelling the growth of pathogens.…”
Section: Notesmentioning
confidence: 99%
“…Super-chilling is a food conservation method that lowers the product’s internal temperature to below 0 °C between conventional chilling and freezing [ 9 ]. The term “super-chilling” has been interchangeably used with terms like “supercooling”, “sub-chilling”, “deep chilling”, “ultra-chilling”, “surface freezing”, and “partial freezing” [ 10 , 11 ]. This definition is currently not explicitly defined in the legislation [ 11 ], although several studies define super-chilling as lowering the internal temperature 1–2 °C below the freezing point of the product, with a certain degree of ice crystal formation [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The term “super-chilling” has been interchangeably used with terms like “supercooling”, “sub-chilling”, “deep chilling”, “ultra-chilling”, “surface freezing”, and “partial freezing” [ 10 , 11 ]. This definition is currently not explicitly defined in the legislation [ 11 ], although several studies define super-chilling as lowering the internal temperature 1–2 °C below the freezing point of the product, with a certain degree of ice crystal formation [ 11 , 12 , 13 , 14 ]. In this study, our focus is to lower the product’s internal temperature to that below melting ice down to the initial freezing point, with no formation of ice crystals.…”
Section: Introductionmentioning
confidence: 99%